D DO SOCIO-DEMOGRAPHIC AND SOCIO-CULTURAL FACTORS IMPACT ON COVID-19 VACCINATION UPTAKE IN NORTH KIVU PROVINCE? - bateyi-mustafa, stephane-hans; Basuayi, Clement Bula; Onyango.O, Rosebella (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
The Sustainable Development Goals three (SDG3) highlighted that immunization impacts directly on health and it does contribute to 14 out of the 17 Sustainable Development Goals (SDGs), such as ending poverty, reducing hunger, and reducing inequalities especially in low and middle-income countries. However, there is no insight related to the role that play by socio-demographic, cultural, geographical distance, psychological, behavioural factors towards the low COVID-19 vaccination uptake. In order to fill this gap in the existing literature review, this paper has used random sample of 2123 people living in North Kivu, logistic and multiple linear regression to investigate, analyze and assess the effects of socio-demographic, geographical distance, psychological, behavioural factors that are driving the COVID-19 vaccine in the Province of Nord Kivu, which province was victim of outreach Ebola and pandemic of COVID-19. The results revealed that males were likely to adhere to COVID-19 vaccine than females, old people were 4 times to adhere to COVID-19 vaccine compared to young people and the high educated people were 3 times to adhere to COVID-19 vaccine than people with low education, catholic church believers were majority to adhere to COVID-19 vaccine compared to others churches, geographical distance, psychological, behavioural affect adherence to COVID-19 at 30.5%. The results from this study inform policymakers and health system to engage with sensitization, communication and training as strategies for increasing the adhere to COVID-19 vaccine among females, young and low educated people and leaders of churches and communities.